Deconstructing the Translation of Psychological Tests - Bolaños-Medina, Alicia; González-Ruiz, Víctor (Meta)

(untitled) (Les Presses de l’Université de Montréal, 2012)
The translation of psychological tests has become widespread as the globalization process has led to testing instruments designed in one country being applied in a different one relatively quickly, since it is less expensive and faster to adapt an existing instrument than to devise a new one in another culture. In order to provide a fully functional version of a test in a different language and culture, the whole cultural context within which a particular test is to be used must be considered, and it is not certain that this has always been the case. This review article explains the peculiarities of psychological tests as a genre and documents the process of translation which has traditionally been used. It is shown that while psychologists have increasingly become aware of the role of cultural context, they have mistakenly regarded this as an issue which is separate from the translation process. That concern for the cultural context is part and parcel of translation itself, is illustrated both in modern translation theory and in current translation practice.